Molecular and Biological Characterization of the First Mymonavirus Identified in Fusarium oxysporum - Wang, Jing; Li, Chengjun; Song, Pengyu; Qiu, Rui; Song, Ruifang; Li, Xiaojie; Ni, Yunxia; Zhao, Hui; Liu, Hongyan; Li, Shujun (Frontiers in Microbiology, 2022)
We characterized a negative single-stranded RNA mycovirus, Fusarium oxysporum mymonavirus 1 (FoMyV1), isolated from the phytopathogenic fungus Fusarium oxysporum. The genome of FoMyV1 is 10,114 nt, including five open reading frames (ORFs1–5) that are nonoverlapping and linearly arranged. The largest, ORF5, encodes a large polypeptide containing a conserved regions corresponding to Mononegavirales RNA-dependent RNA polymerase (RdRp) and mRNA-capping enzyme region V; the putative functions of the remaining four ORFs are unknown. The RdRp encoded by ORF5 shared a high amino acid identity of 65% with that of Hubei rhabdo-like virus 4, a mymonavirus that infects invertebrates. However, the RdRp of FoMyV1 also showed amino acid similarity (27%–36%) with proteins of mynonaviruses that infect the phytopathogenic fungi Sclerotinia sclerotiorum and Botrytis cineaea. Phylogenetic analysis based on RdRp showed that FoMyV1 is clustered with the members of the genus Hubramonavirus in the family Mymonaviridae. Moreover, we found that FoMyV1 could successfully transfer by hyphal anastomosis to a virus-free strain. FoMyV1 reduced the vegetative growth and conidium production of its fungal host but did not alter its virulence. To the best of our knowledge, this is not only the first mymonavirus described in the species F. oxysporum, but also the first Hubramonavirus species found to infect a fungus. However, the incidence of FoMyV1 infections in the tested F. oxysporum strains was only 1.4%.